2021
DOI: 10.1016/j.jcyt.2020.12.003
|View full text |Cite
|
Sign up to set email alerts
|

1,25-dihydroxyvitamin D3 induces stable and reproducible therapeutic tolerogenic dendritic cells with specific epigenetic modifications

Abstract: Autologous, antigen-specific, tolerogenic dendritic cells (tolDCs) are presently assessed to reverse and possibly cure autoimmune diseases such as type 1 diabetes (T1D). Good Manufacturing Practice production and clinical implementation of such cell therapies critically depend on their stability and reproducible production from healthy donors and, more importantly, patient-derived monocytes. Here the authors demonstrate that tolDCs (modulated using 1,25-dihydroxyvitamin D3 and dexamethasone) displayed similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…Single-cell heatmap overlay of selected immune markers demonstrated a progressive increase of HLA-DR and CD86 with maturation in control wells, which was reduced in both tolerogenic counterparts. Consistent with previous reports 12 , 38 , tol-DC exhibited a robust increase in CD14, CD141, and ILT3, and PD-L1 across all maturation stages (Fig. 4A , Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
“…Single-cell heatmap overlay of selected immune markers demonstrated a progressive increase of HLA-DR and CD86 with maturation in control wells, which was reduced in both tolerogenic counterparts. Consistent with previous reports 12 , 38 , tol-DC exhibited a robust increase in CD14, CD141, and ILT3, and PD-L1 across all maturation stages (Fig. 4A , Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, only five of these genes were also reported as direct targets of VDR ( 170 ), leaving others to an indirect control by VDR-targeted transcription factors. Of the direct VitD3-targets, the expression of ORMDL3 , SH2B3 , IKZF1 , PTPN2 and IFIH1 genes was lower in tolDC while RAC2 and PTPN22 were higher in tolDC than in the inflammatory mDCs ( 17 , 18 ).…”
Section: Tolerogenic Modulation Of Dendritic Cells and The Impact On ...mentioning
confidence: 99%
“…This natural immunomodulator influences the development and function of T cells, B cells and monocytes ( 172 , 174 , 175 ), and controls the ability of the immune system to dampen inflammation. In two independent studies we found that about a third of the transcripts encoded by non-HLA T1D risk genes were differentially expressed between inflammatory mDCs and VitD3-derived tolDCs ( 17 , 18 ). Interestingly, only five of these genes were also reported as direct targets of VDR ( 170 ), leaving others to an indirect control by VDR-targeted transcription factors.…”
Section: Tolerogenic Modulation Of Dendritic Cells and The Impact On ...mentioning
confidence: 99%
See 2 more Smart Citations